2007
DOI: 10.1108/01443580710817443
|View full text |Cite
|
Sign up to set email alerts
|

Impact of political changes on industrial efficiency: a case of Ukraine

Abstract: PurposeThe paper aims to devote itself to the researching of the changes in firm efficiency in consumer goods industry under the political changes and tightening of competition. This study has for an objective the estimation of the consequences of changes in policy on firm efficiency and the development the ways of improving of the efficiency of both separate firms and the whole industries.Design/methodology/approachThe industrial efficiency is measured by data envelopment analysis (DEA). The change of efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Margono and Sharma (2006) and Kong et al (1999) reported productivity declines in Indonesia and China, respectively. Goncharuk (2007) found a large productivity decline of 7.29 % for Ukraine. Taymaz and Saatçi (1997) found rapid technical progress (6 %) for Turkish textile and clothing firms.…”
Section: Introductionmentioning
confidence: 97%
“…Margono and Sharma (2006) and Kong et al (1999) reported productivity declines in Indonesia and China, respectively. Goncharuk (2007) found a large productivity decline of 7.29 % for Ukraine. Taymaz and Saatçi (1997) found rapid technical progress (6 %) for Turkish textile and clothing firms.…”
Section: Introductionmentioning
confidence: 97%
“…In the output-oriented models, outputs are maximized while using no more than the observed amount of any input (Duzakin & Duzakin, 2007;Charnes, Cooper & Rhodes, 1978;Banker, Based on the mathematical programming theory, DEA is an efficiency evaluation method which creates an optimization for the individual observation by evaluating a discrete piece-wise frontier. Efficiency refers to the quotient from the division of the sum of all outputs by the sum of all inputs (Goncharuk, 2007). In data envelopment analysis, the frontier is found out by the set of Pareto efficient decision management units (Tongzon, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, it can consider more than one output whereas it does not require the determination of the priority issues among the inputs and outputs (Tongzon, 2001). Moreover, DEA in efficiency measurement eliminates the problems that can lead to wrong results of the efficiency measurement in which only the separate production factors are isolated (Goncharuk, 2007). Cubbin and Tzanidakis (1998) reveal that DEA is good at identifying possible reasons for poor performances by providing a checklist for the management staff.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention shall be paid to scientific developments on the range of problems in industrial and mechanical engineering in countries that develop their economic systems (Lister and Donaldson 2004;Sami El-Khasawneh 2012;Tybout 2000), including in the states that were part of the USSR (Goncharuk 2007;Krivokon 2016;Saifieva and Yermilina 2008;Tashenov 2013).…”
Section: Introductionmentioning
confidence: 99%